DEVELOPMENT OF ELECTRONIC STUDENT WORKSHEETS BASED ON PROBLEM-BASED LEARNING USING INTERACTIVE COMICS ON REACTION RATE MATERIAL - Rachmi, Naila Syabina; Simatupang, Lisnawaty (Chimica Didactica Acta, 2025)
This study aims to determine the feasibility of electronic student worksheets (e-SWS) based on Problem-Based Learning assisted by interactive comic media on the material of reaction rate and student responses, and teachers using electronic student worksheets (e-SWS) based on Problem-Based Learning assisted by interactive comic media on the material of reaction rate. This study is a research and development (RD) project utilizing the ADDIE development model (analysis, design, development, implementation, and evaluation), focusing on the implementation stage, including field trials. The study results were obtained with an average material validation of 75 percent and an average media expert validation of 89.06 percent; through these data, the results of product validation from material and media experts were 82.03 percent, with a very valid category and feasible to use. In the acquisition of field trial data, the average student response was 82.72 percent, with a very positive category for use, and the results of teacher responses were obtained at 96.73 percent, with a very positive category. So, electronic student worksheets (e-SWS) based on Problem-Based Learning, assisted by interactive comic media on reaction rate material, are feasible. They can be used as teaching materials in the learning process.